2021
DOI: 10.1590/2177-9465-ean-2020-0546
|View full text |Cite
|
Sign up to set email alerts
|

Custos catastróficos em pacientes com tuberculose no Brasil: estudo em cinco capitais

Abstract: Resumo Objetivo avaliar o impacto econômico domiciliar do adoecimento pela tuberculose no Brasil. Método pesquisa transversal multicêntrica de 2016 a 2018, em cinco capitais do Brasil, em pacientes diagnosticados com tuberculose. Os custos totais foram a soma dos custos diretos e indiretos incorridos antes e durante o diagnóstico e tratamento. A regressão logística foi utilizada para estudar determinantes de custos catastróficos. A pobreza foi medida como renda familiar per capita diária < U$ 5,5. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 17 publications
1
7
0
5
Order By: Relevance
“…In our study we found that 44.4% DS-TB-affected households and 78.5% DR-TB-affected households experienced catastrophic costs due to the disease. Our result for DR-TB patients and their households is consistent with the findings of the Rio de Janeiro’s study where 68% of DR-TB patients experienced catastrophic costs due to TB [ 24 ]. Based on these results social protection measures could be specifically evaluated for DR-TB patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In our study we found that 44.4% DS-TB-affected households and 78.5% DR-TB-affected households experienced catastrophic costs due to the disease. Our result for DR-TB patients and their households is consistent with the findings of the Rio de Janeiro’s study where 68% of DR-TB patients experienced catastrophic costs due to TB [ 24 ]. Based on these results social protection measures could be specifically evaluated for DR-TB patients.…”
Section: Discussionsupporting
confidence: 91%
“…A study by Guidoni L.M. et al, conducted in five large cities in Brazil, found that on average income of participants declined by 11% during the TB episode and 41% faced direct and indirect costs that were higher than 20% of self-reported household income prior to TB [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tal situação pode ocasionar o rompimento de relações, contribuindo para a fragilidade da rede. Os enfermeiros e demais profissionais da saúde devem estar sempre atentos à ineficácia da rede social, que pode levar ao abandono do tratamento, agravamento da doença e manutenção da cadeia de transmissão, além do aumento de custos catastróficos durante o período de tratamento da TB 12,[20][21] .…”
Section: Discussionunclassified
“…Such a situation can cause rupture of relationships, contributing to fragility of the network. Nurses and other health professionals should always be aware of the ineffectiveness of a social network, which can lead to treatment abandonment, disease worsening and maintenance of the transmission chain, in addition to increased catastrophic costs during the TB treatment period 12,[20][21] .…”
Section: /11mentioning
confidence: 99%